EVALUASI KEBERLANJUTAN PENERAPAN LANGKAH-LANGKAH BIOSEKURITI PADA PETERNAKAN AYAM BROILER DI DESA SELANBAWAK, KECAMATAN MARGA, KABUPATEN TABANAN - N. P., SARINI; SURYANI, N. N.; MARIANI, NI PUTU; OKA, A. A.; DEWANTARI, M. (Majalah Ilmiah Peternakan; Vol 21 No 2 (2018): Vol 21, No 2 (2018), 2018)
The entry of Avian Influenza (AI) to Indonesia in 2003 gave a tremendously negative impact on poultry businesses. Biosecurity is one of the government efforts to protect the spread of infectious diseases to the farms. It gets a good response from all the stakeholders in the poultry industry. Although there are no Avian Influenza outbreaks anymore, control to the Highly Pathogenic Avian Influenza (HPAI) is still becoming a main priority in controlling diseases in the poultry farms. This research was conducted to evaluate the sustainability of biosecurity implementation in the broiler farms and mentored requirement to prevent AI outbreaks from occurring again. A survey was used to gain information on broiler famers at Selanbawak Village. The samples in this study were all the farmers who were involved in the ACIAR project AH/2006/169. They had been trained and supervised to implement biosecurity measures in their farms. The data obtained were descriptive-qualitatively analyzed using percentage approach based on the biosecurity implementation criteria. It was found that the biosecurity measures implemented by those farmers had not been maintained. Most of the farms were untidy; and rubbishes and bushes were scattered around the farms. The footbath was not properly used as sanitary equipment, and even some were buried with cement.